The Border Between Science and Science-Fiction is Fading Out - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
The scientific development of human civilization cannot be described as a linear progression, but rather as a stepwise catapulting process, depending on the control and severity of regulations imposed by rulers and religious authorities. While the development of arts like painting and sculpturing constantly proceeded, advancements in science, medicine, and philosophy have shown a slower progress. This imbalance shrank toward the end of the Industrial Revolution with the lift of religious and monarch control and the establishment of urban societies with educational systems, communication networks, and improvements in human rights and freedom of mind. Strikingly, while nearing the end of the previous millennium, the spiritual and social advancements were accompanied by an overwhelming upgrade of life standards.